Existence of positive solutions for nonlinear third-order m-point impulsive boundary value problems on time scales - Fen, F. T.; Karaca, I. Y. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
In the paper, the four functionals fixed-point theorem is used to study the existence of positive solutions for nonlinear thirdorder m-point impulsive boundary-value problems on time scales. As an application, we give an example demonstrating our results.